Implementasi Kurikulum Merdeka Dalam Meningkatkan Hasil Belajar Siswa MAN 2 Langsa: (Implementation of the deep independent curriculum improves learning outcomes MAN 2 langsa students) - Lestari, Indah Lepi; Sarjani, Tri Mustika; Wahyuni, Ayu (BIODIK, 2025)
This research aims to determine whether implementing the independent curriculum can improve the learning outcomes of MAN 2 Langsa students. To find out how implementing the independent curriculum improves the learning outcomes of MAN 2 Langsa students. The method used in this research is qualitative descriptive, using interviews, observation, and documentation instruments. The sample in this study consisted of two biology teachers who taught in class X and eight students in class X at MAN 2 Langsa, who were divided into two classes. The research results show that implementing the Merdeka Curriculum in Improving Student Learning Outcomes at MAN 2 Langsa can improve student learning outcomes significantly, namely increasing by 100% from class XB, and student learning outcomes from class XE also increased significantly by 95.6 %. Implementing the Independent Curriculum in Improving MAN 2 Langsa Student Learning Outcomes is carried out by planning learning based on the independent curriculum; the teacher has prepared a Flow of Learning Objectives (ATP) and teaching modules. The implementation of the independent curriculum in the results of this research has two answers namely where the answers from students are that they are ready with the independent curriculum with P5 activities, they are happy to take part in these activities and according to them, apart from the lessons they like, they can improve their learning outcomes, P5 activities can also improve their learning outcomes. Meanwhile, the teacher stated that the independent curriculum had been implemented well, but there were still weaknesses. The weakness is that the school still lacks the facilities and infrastructure to implement the independent curriculum at MAN 2 Langsa. Abstrak. Penelitian ini bertujuan untuk mengetahui apakah implementasi kurikulum merdeka dapat meningkatkan hasil belajar siswa MAN 2 Langsa. Untuk mengetahui bagaimana implementasi kurikulum merdeka dalam meningkatkan hasil belajar siswa MAN 2 Langsa. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif dengan menggunakan instrumen wawancara, observasi dan dokumentasi. Sampel pada penelitian ini adalah 2 guru biologi yang mengajar di kelas X dan 8 siswa kelas X MAN 2 Langsa yang terbagi menjadi 2 kelas. Hasil penelitian menunjukkan bahwa Hasil penelitian menunjukkan bahwa Implementasi Kurikulum Merdeka dalam Meningkatkan Hasil Belajar Siswa MAN 2 Langsa dapat meningkatkan hasil belajar siswa secara signifikan yaitu meningkat sebesar 100% dari kelas XB dan hasil belajar siswa dari kelas XE juga mengalami peningkatan secara signifikan sebesar 95,6 %. Implementasi Kurikulum Merdeka dalam Meningkatkan Hasil Belajar Siswa MAN 2 Langsa dilakukan dengan perencanaan pembelajaran berdasarkan kurikulum merdeka guru sudah menyiapkan Alur Tujuan Pembelajaran (ATP) dan modul ajar. Implementasi kurikulum merdeka dalam hasil penelitian ini memiliki dua jawaban yaitu dimana jawaban dari siswa bahwa mereka sudah siap dengan adanya kurikulum merdeka dengan kegiatan P5 mereka dengan senang mengikuti kegiatan tersebut dan menurut mereka selain pelajaran yang mereka sukai dapat meningkatkan hasil belajar mereka, kegiatan P5 juga dapat meningkatkan hasil belajar mereka. Sementara itu, guru menyatakan bahwa implementasi kurikulum merdeka ini sudah terlaksanakan dengan baik namun masih terdapat kelemahan. Kelemahannya yaitu pada implementasi kurikulum merdeka di MAN 2 Langsa masih kurangnya sarana dan prasarana di sekolah.